A Study of Correlations among Personal Factors, Selected Clinical Determinants, and Risk Behaviours in Patients with Accidental Injuries - Yaowares, Piyaporn; Chayaput, Prangtip; Poonkate, Amonrut; Kliangda, Chaninthorn (Journal of Thailand Nursing and Midwifery Council, 2022)
Objective: To investigate the correlations between personal characteristics (i.e., age and gender), selected clinical determinants (i.e., causes of injuries, mechanisms of injuries,number of injured body parts, injured body parts, severity of injuries, and complications), and risk behaviours, and to compare the differences in severity of injury and complications between patients with risk behaviours and those without risk behaviours Design: Retrospective descriptive correlational and comparative research design Methodology: The participants were 122 accidental injury patients admitted to a super-tertiary care hospital in Bangkok. The number of recruited participants were determined in proportion to the number of each year’s injured patients. Then the method of quota sampling for eligible patients based on the calculated sample size was employed. Data were gathered retrospectively from the patients’ chart and medical records. Research tools consisted of personal information and clinical data record form, and a questionnaire for severity of injuries and complications. Chi-square Test and Fisher’s Exact Test for correlations were employed for data analysis, whilst Mann-Whitney U test was conducted for comparisons of severity of injuries and complications. Results: Age, gender, cause of injury, number of injured body parts, injured body parts, and severity of injury were related to risk behaviours. Additionally, risk behaviours, including smoking and alcohol drinking, had signifcant correlations with severity of injury, but were not related with complications. Signifcant differences in injury severity levels were found between those with risk behaviours and those without, whereas no differences in complications were identifed. Recommendations: Personal characteristics and some selected clinical determinants showed signifcant relationships with risk behaviours. Injury severity levels differed amongst smokers and alcohol drinkers. Thus, nurses can utilise the empirical evidence to complement the healthcare policy and promote education and awareness of accident risk caused by risk behaviours including smoking and alcohol consumption, so as to reduce severity of injury from accidents and promote recovery after injury.